Creative People and Gentrification: “Sowing the Seeds of Demise?” Evidence from Newtown , Sydney - Fasche, Melanie (ERDKUNDE, 2006)
The post-industrial economy is associated with the shift from the Fordist to the Post-Fordist economy where design-orientated, information-rich companies work within a new flexible mode of production. The sectors engaged in producing cultural goods and services constitute some of the most dynamic economic frontiers today. Small creative businesses, also imagined to be the major driver for innovation within the cultural industries, tend to locate away from established business centres but close to areas known for their cultural amenities, urban lifestyles and artistic scene. People employed in cultural industries seem to have a special relationship to their working and living environment. Local marketing campaigns are based on this cultural claim to space. With proceeding gentrification areas might loose their attractiveness for creative people. The focus of this study is on a neighbourhood undergoing gentrification, creative people living and working within this neighbourhood and the influence of local government policies. The relationship between the specific place and cultural production gets analysed closer before it is examined if the process of gentrification is damaging the viability of the cultural realm and to which extent the influence of local politics can mediate between cultural and economic interest. By drawing on case-study evidence from Newtown , one of Sydney ’s inner city areas, it is aimed at demonstrating that the complex relationship between space and society can be conceptualized in terms of Bourdieu’s habitus concept.